Neuromodulation Strategies to Reduce Inflammation and Improve Lung Complications in COVID-19 Patients - Czura, Christopher J.; Bikson, Marom; Charvet, Leigh; Chen, Jiande D. Z.; Franke, Manfred; Fudim, Marat; Grigsby, Eric; Hamner, Sam; Huston, Jared M.; Khodaparast, Navid; Krames, Elliot; Simon, Bruce J.; et al. (Frontiers in Neurology, 2022)
Since the outbreak of the COVID-19 pandemic, races across academia and industry have been initiated to identify and develop disease modifying or preventative therapeutic strategies has been initiated. The primary focus has been on pharmacological treatment of the immune and respiratory system and the development of a vaccine. The hyperinflammatory state (“cytokine storm”) observed in many cases of COVID-19 indicates a prognostically negative disease progression that may lead to respiratory distress, multiple organ failure, shock, and death. Many critically ill patients continue to be at risk for significant, long-lasting morbidity or mortality. The human immune and respiratory systems are heavily regulated by the central nervous system, and intervention in the signaling of these neural pathways may permit targeted therapeutic control of excessive inflammation and pulmonary bronchoconstriction. Several technologies, both invasive and non-invasive, are available and approved for clinical use, but have not been extensively studied in treatment of the cytokine storm in COVID-19 patients. This manuscript provides an overview of the role of the nervous system in inflammation and respiration, the current understanding of neuromodulatory techniques from preclinical and clinical studies and provides a rationale for testing non-invasive neuromodulation to modulate acute systemic inflammation and respiratory dysfunction caused by SARS-CoV-2 and potentially other pathogens. The authors of this manuscript have co-founded the International Consortium on Neuromodulation for COVID-19 to advocate for and support studies of these technologies in the current coronavirus pandemic.